2007
DOI: 10.1016/j.chiabu.2006.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver commitment to foster children: The role of child behavior

Abstract: Objective: This study aimed to examine the association between child behavior problems and caregiver commitment to their child in a group of young foster children. Method:The sample consisted of 102 caregiver-child dyads from the greater Baltimore area. Child behavior was assessed using the Child Behavior Checklist (CBCL; Achenbach, 1991Achenbach, ,1992, and caregiver commitment was assessed using a semi-structured interview known as the "This is My Baby" Interview (Bates & Dozier, 1998). For a sub-sample of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 15 publications
2
44
1
1
Order By: Relevance
“…The strongest predictor of placement disruptions is externalizing behaviors by foster children that exceed their foster parents' capacity to manage them (Barber, Delfabbro, & Cooper, 2001;Leathers, 2006;Lindhiem & Dozier, 2007;Newton, Litrownik, & Landsverk, 2000;Oosterman, Schuengel, Slot, Bullens, & Doreleijers, 2007). Results have been mixed in studies on the impact of the most widely used foster parent training programs, such as MAPP and PRIDE, in training foster parents with strategies and skills in managing disruptive and confrontational behaviors (Christenson & McMurtry, 2007;Puddy & Jackson, 2003).…”
Section: Unsuccessful Transitionsmentioning
confidence: 95%
“…The strongest predictor of placement disruptions is externalizing behaviors by foster children that exceed their foster parents' capacity to manage them (Barber, Delfabbro, & Cooper, 2001;Leathers, 2006;Lindhiem & Dozier, 2007;Newton, Litrownik, & Landsverk, 2000;Oosterman, Schuengel, Slot, Bullens, & Doreleijers, 2007). Results have been mixed in studies on the impact of the most widely used foster parent training programs, such as MAPP and PRIDE, in training foster parents with strategies and skills in managing disruptive and confrontational behaviors (Christenson & McMurtry, 2007;Puddy & Jackson, 2003).…”
Section: Unsuccessful Transitionsmentioning
confidence: 95%
“…Commitment and problem behaviors are not only inversely related contemporaneously, but also predict one another at subsequent time-points (Lindhiem & Dozier, 2007). More specifically, greater commitment at time 1 predicts fewer problem behaviors at time 2, controlling for problem behaviors at time 1; more problem behaviors at time 1 predicts less commitment at time 2, controlling for commitment at time 1.…”
Section: Commitmentmentioning
confidence: 99%
“…We hypothesized that caregivers in foster parent settings would display higher amounts of commitment than caregivers in the two residential group home settings. Given that previous studies found problem behaviors differentially related to both care-type (Heflinger et al, 2000; Ryan et al, 2008) and caregiver commitment (Lindhiem & Dozier, 2007), we also accounted for differences in problem behaviors between youth in foster and group care. Given the known associations between number of children cared for and commitment (Dozier and Lindhiem, 2006), we also account for differences in the number of children caregivers have cared for between youth in foster and group care.…”
Section: Commitmentmentioning
confidence: 99%
“…Comparison of these available results with the United States and Mexico groups indicates that the Mexico group had equal or higher T scores for most of the scales, with few exceptions (e.g., sleep problems). When compared to children with mild/severe brain injury, 62 single-suture craniosynostosis, 63 parental history of cocaine, alcohol, tobacco, and marijuana exposure, 64 prenatal cocaine exposure, 65 maternal current and past depression, 66 and hearing impairment, 67 children in the Mexico group had significantly higher scores for most scales. A smaller number of scales were similar and non-significant when compared with the Mexico group, with a reduced number of higher scales and significant differences in the same group.…”
Section: Resultsmentioning
confidence: 99%